Tryptophan Supplementation Enhances Intestinal Health by Improving Gut Barrier Function, Alleviating Inflammation, and Modulating Intestinal Microbiome in Lipopolysaccharide-Challenged Piglets - Liu, Guangmang; Lu, Jiajia; Sun, Weixiao; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Kim, In Ho; Zhang, Ruinan; Wang, Jing (Frontiers in Microbiology, 2022)
Tryptophan (Trp) can modify the gut microbiota. However, there is no information about the effect of Trp on intestinal microbiota after lipopolysaccharide (LPS) challenge. This study aimed to investigate the effect of Trp on intestinal barrier function, inflammation, antioxidant status, and microbiota in LPS-challenged piglets. A total of 18 weaned castrated piglets were randomly divided into three treatments with 6 replicate per treatment, namely, (i) non-challenged control (CON); (ii) LPS-challenged control (LPS-CON); and (iii) LPS + 0.2% Trp (LPS-Trp). After feeding with control or 0.2% tryptophan-supplemented diets for 35 days, pigs were intraperitoneally injected with LPS (100 μg/kg body weight) or saline. At 4 h post-challenge, all pigs were slaughtered, and colonic samples were collected. The samples were analyzed for gut microbiota, fatty acids, antioxidant parameters, and the expression of mRNA and protein. The community bar chart showed that Trp supplementation to LPS-challenged pigs increased the relative abundance of Anaerostipes (P < 0.05) and tended to increase the relative abundance of V9D2013_group (P = 0.09), while decreased the relative abundance of Corynebacterium (P < 0.05) and unclassified_c__Bacteroidia (P < 0.01). Gas chromatography showed that Trp increased the concentrations of acetate, propionate, butyrate, and isovalerate in the colonic digesta (P < 0.05). Trp reduced the mRNA level of pro-inflammatory cytokines (P < 0.01), and increased mRNA level of aryl hydrocarbon receptor, cytochrome P450 (CYP) 1A1 and CYP1B1 (P < 0.05). Correlation analysis results showed that acetate, propionate, and butyrate concentrations were positively correlated with mRNA level of occludin and CYP1B1 (P < 0.05), and were negatively correlated with pro-inflammatory cytokines gene expression (P < 0.05). Isovalerate concentration was positively correlated with catalase activity (P < 0.05), and was negatively correlated with pro-inflammatory cytokines gene expression (P < 0.05). Furthermore, Trp enhanced the antioxidant activities (P < 0.01), and increased mRNA and protein expressions of claudin-1, occludin, and zonula occludens-1 (P < 0.01) after LPS challenge. These results suggest that Trp enhanced intestinal health by a modulated intestinal microbiota composition, improved the short chain fatty acids synthesis, reduced inflammation, increased antioxidant capacity, and improved intestinal barrier function.